Impact of neoadjuvant chemotherapy on survival in breast cancer patients in daily practice: a population‐based study. (5th May 2013) - Dabakuyo, T.S.; Arnaud, A.; Maingon, P.; Causeret, S.; Coudert, B.; Fumoleau, P.; Arnould, L.; Poillot, M.‐L.; Arveux, P.; Crehange, G.; Bonnetain, F.
<x xml:space="preserve">Abstract</x> This population‐based study aimed to describe the effects of neoadjuvant chemotherapy (NC) on survival in breast cancer (BC) patients in daily practice. BC patients treated with NC followed by surgery and radiotherapy, were retrospectively selected from 1982 to 2005 using the Côte d'Or BC registry. These patients were matched for the baseline AJCC (American Joint Committee on Cancer) stage, age at diagnosis, date of diagnosis and oestrogens receptors status to those who had undergone surgery followed by adjuvant chemotherapy and radiotherapy. The prognostic effect of NC on survival in BC patients was assessed with relative survival (RS) analyses. From 1982 to 2005, 210 patients with BC diagnosed in Côte d'Or were treated with NC followed by surgery and radiotherapy. For these patients, mean age at diagnosis was 50 (SD = 11). The main tumour characteristics were clinical AJCC stage 3 (46%) and an advanced Scarff Bloom and Richardson (SBR) stage (80%). Breast conserving surgery was performed in 84 patients (40%), 151 patients (72%) were treated with anthracyclines as the NC and the 5‐year RS rate was 71%. Among these patients, 92 (37%) were matched. In this population, multivariate analyses showed that the use of NC did not independently influence RS: relative excess risk = 0.93 (0.50, 1.71).